Precision therapy for three Chinese families with maturity-onset diabetes of the young (MODY12) - Li, Juyi; Wang, Xiufang; Mao, Huihui; Wen, Li; Deng, Aiping; Li, Yarong; Zhang, Hongmei; Liu, Chao (Frontiers in Endocrinology, 2022)
Maturity-onset diabetes of the young (MODY) is a rare monogenic diabetes. However, MODY is often undiagnosed or misdiagnosed. In this study, we aimed to investigate the pathogenic gene of diabetes and provide precise treatment for diabetic patients in three families. Three families with suspected MODY were enrolled and screened for germline mutations using Whole exome sequencing (WES). Candidate pathogenic variants were validated in other family members and non-related healthy controls. Three heterozygous missense mutations in ABCC8 gene (NM_001287174), c.1555 C>T (p.R519C), c.3706 A>G (p.I1236V), and c.2885 C>T (p.S962L) were found in family A, B, and C, respectively. All mutation sites cosegregated with diabetes, were predicted to be harmful by bioinformatics and were not found in non-related healthy controls. Two probands (onset ages, 8 and 12 y) were sensitive to glimepiride; however, if the dose is not enough (2 mg/daily), which led to ketoacidosis. When increased the dosage of glimepiride (4 mg/ daily), blood sugar remained under control. Furthermore, 4 mg glimepiride tablets daily also effectively controlled blood sugar in adult patient (25-year-old). In addition, all patients were sensitive to liraglutide, which can better control blood sugar. These data suggest ABCC8 were the pathogenic gene in three families with diabetes. Glimepiride (2 mg/ daily) was not safe for controlling blood sugar in children with ABCC8 mutations, however, 4 mg/ daily glimepiride is safe and effective including children. Moreover, liraglutide was effective in controlling blood sugar in patients with ABCC8 mutations including children.